Artificial Intelligence Based Patient-Specific Preoperative Planning Algorithm for Total Knee Arthroplasty - Lambrechts, Adriaan; Wirix-Speetjens, Roel; Maes, Frederik; Van Huffel, Sabine (Frontiers in Robotics and AI, 2022)
Previous studies have shown that manufacturer’s default preoperative plans for total knee arthroplasty with patient-specific guides require frequent, time consuming changes by the surgeon. Currently, no research has been done on predicting preoperative plans for orthopedic surgery using machine learning. Therefore the goal of this study is to evaluate whether artificial intelligence (AI) driven planning tools can create surgeon and patient-specific preoperative plans that require fewer changes by the surgeon. A dataset of 5409 preoperative plans including the manufacturer's default and the plans corrected by 39 surgeons were collected. Features were extracted from the preoperative plans that are descriptive of the implant sizes, position and orientation in a surgeon- and patient-specific manner. Based on these features, non-linear regression models were employed to predict the surgeon corrected preoperative plan. The average number of corrections a surgeon has to make to the preoperative plan generated using AI was reduced by 39.7% compared to the manufacturer’s default plan. The femoral and tibial implant size in the manufacturer’s plan was correct in 68.4% and 73.1% of the cases respectively, while the AI based plan was correct in 82.2% and 85.0% of cases respectively compared to the surgeon approved plan. Our method successfully demonstrated the use of machine learning to create preoperative plans in a surgeon and patient-specific manner for total knee arthroplasty.